2016
DOI: 10.1002/dc.23505
|View full text |Cite
|
Sign up to set email alerts
|

The potential of identification of a malignancy‐associated biomarker in breast cancer diagnosis and research: hTERT gene DNA methylation

Abstract: We believe that integration of this novel, malignancy-associated molecular testing with morphology is of significant value in the accurate interpretation of small tumor sample size obtained via fine needle aspiration biopsy, ductal lavage, and nipple fluid aspirates both in clinical practice and in breast cancer research. Diagn. Cytopathol. 2016;44:670-675. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The analyses revealed hTERT hypermethylation in tumors and surrounding tissues of all patients. This is very similar to the results reported by Masood et al, 19 who found that 94% of breast carcinomas displayed hypermethylation levels at least 2-fold higher than those measured in normal breast tissue. In contrast, in our study, only five of the fifteen patients presented hTERT methylation in their cfDNA.…”
Section: Discussionsupporting
confidence: 92%
“…The analyses revealed hTERT hypermethylation in tumors and surrounding tissues of all patients. This is very similar to the results reported by Masood et al, 19 who found that 94% of breast carcinomas displayed hypermethylation levels at least 2-fold higher than those measured in normal breast tissue. In contrast, in our study, only five of the fifteen patients presented hTERT methylation in their cfDNA.…”
Section: Discussionsupporting
confidence: 92%
“…The efficacy of contrast-enhanced MRI in the diagnosis of breast cancer has been previously proven ( 29 ). In addition, diagnosis of breast cancer using malignancy-associated biomarkers has been widely accepted ( 30 ). The present study analyzed the efficacy of the combination of MRI and detection of gene expression in diagnosing patients with breast cancer in the early stage.…”
Section: Discussionmentioning
confidence: 99%
“…In the same time, an optimal combination of genes, which methylation could provide important clinical data, has not been defined yet. The results of our study of methylation in small breast cancer tumors can be useful for cancer identification in small samples obtained by needle biopsy, where cancer is sometimes missed [8]. An important aspect of the study of methylation in small tumors is selection of potential markers for effective early diagnosis of breast cancer by detection of circulating cancer DNA in plasma [9].…”
Section: Discussionmentioning
confidence: 99%